American Telephone and Telegraph Company Exhibit Building, New York World's Fair 1939 (Grinnell Litho Co.)
Utilizing the forms common to the telephone industry the designers of this building have created an unusual architectural form. The entrance to the exhibit area is through a semi-circular court into a primitive grove containing pools and fountains. The visitor to this building is given an inside view of the workings of the telephone industry.